A novel operando approach to analyze the structural evolution of metallic materials during friction with application of synchrotron radiation. (1st September 2020) - Bataev, I.A.; Lazurenko, D.V.; Bataev, A.A.; Burov, V.G.; Ivanov, I.V.; Emurlaev, K.I.; Smirnov, A.I.; Rosenthal, M.; Burghammer, M.; Ivanov, D.A.; Georgarakis, K.; Ruktuev, A.A.; et al.
Abstract: In this study, we describe an experimental setup and a new approach for operando investigation of structural evolution of materials during wear and friction. The setup is particularly suited for testing various friction pairs, including those in which both rubbing bodies are made of metals. The developed device allows circumventing the problems related to significant scattering of X-rays produced by metals and makes it possible using "real samples" in synchrotron beamlines operating in reflection mode. To demonstrate the capabilities of the device and the proposed new approach, an iron-based massive sample was subjected to thousands of friction cycles using a cemented carbide pin. The material was probed with synchrotron X-ray radiation within a few milliseconds after leaving the friction zone. The results of the microstructural and structural analysis, as well as results obtained from diverse mathematical models, allowed us to evaluate several features, including gradual accumulation of defects, microstructural refinement, dislocation density changes, surface layer oxidation, as well as several other phenomena caused by the dry sliding friction process. Mainly, it was possible to conclude that the process of wear occurred due to the cooperative action of oxidation and plastic deformation, which began during the first cycle of frictional interaction and was manifested in increasing the dislocation density, whose type was changed gradually during testing. The number of defects quickly reached a threshold value and subsequently fluctuated around it due to periodically repeated processes of defect accumulation and stress relaxation resulting from material wear. It was also observed that friction led to the quick formation of a mechanically mixed layer, consisting of the sample material and a mixture of two types of iron oxide – hematite and magnetite. The delamination of this layer was probably the primary wear mechanism. Graphical abstract: Image, graphical abstract